(untitled) (Lex localis - Journal of Local Self-Government, 2025)
This study explores the strengthening of local health governance by analyzing the role of employee competence, adaptability, and commitment in improving hospital service effectiveness, with the mediating role of Electronic-Based Information Systems (EBIS) in Regional General Hospitals (RSUD) in South Sumatra, Indonesia. The research is motivated by the increasing demand for digital transformation in the public healthcare sector and the need to align technological advancement with human capital development to ensure efficient and high-quality service delivery. Using a quantitative design, data were collected through structured questionnaires and analyzed with Structural Equation Modeling (SEM) via AMOS to examine both direct and indirect relationships among the variables. The findings demonstrate that employee competence, adaptability, and commitment significantly enhance EBIS implementation while simultaneously exerting a direct influence on hospital service effectiveness. Moreover, EBIS serves as a crucial mediating mechanism that links employee-related factors to improved service outcomes. These results provide practical implications for hospital administrators, emphasizing the importance of continuous training, workforce adaptability, and strategic use of information systems to achieve more effective and sustainable local health governance. Overall, this study contributes to both theoretical and practical understandings of how human resource dimensions and digital systems interact to strengthen healthcare services in developing regions.